Experience with vertebral artery origin stenting and ostium dilatation: results of treatment and clinical outcomes. (2nd April 2015) - Rangel-Castilla, Leonardo; Gandhi, Sirin; Munich, Stephan A; Cress, Marshall C; Sonig, Ashish; Krishna, Chandan; Hopkins, L Nelson; Snyder, Kenneth V; Levy, Elad I; Siddiqui, Adnan H
Abstract : Background: The vertebral artery (VA) ostium (VAO) is a common stenosis site. Most patients with VAO stenosis refractory to medical treatment are treated endovascularly using stenting. To optimally cover the ostial plaque, which frequently extends into the adjacent subclavian artery, part of the stent must overhang in the subclavian artery. This configuration makes subsequent VA access very challenging in cases of in-stent or distal vertebrobasilar pathology; it also obstructs the distal subclavian artery. Objective: To determine whether angioplasty at the ostium with a dual balloon (Flash Ostial) specially designed to allow the subclavian end of the stent to flare might circumvent these problems and, most importantly, provide optimal plaque coverage around the vertebral ostium. Methods: Between June 2012 and July 2014, 11 patients with symptomatic VAO stenosis refractory to best medical therapy were treated with stenting and dual balloon Flash angioplasty. Demographics, results, and outcomes were reviewed. Results: A total of 12 VAO stenting–dual balloon angioplasty procedures were performed (mean stenosis, 83.6%; range, 78–90%). Nine patients had mild-to-moderate (40–60%) contralateral VAO stenosis. The initial average modified Rankin Scale (mRS) score was 1.25. In all cases, immediate postangioplasty angiography showed excellent stent apposition against the VA and around the ostium in the subclavian artery. No permanent perioperative complications or deaths occurred. At a mean follow-up of 10.8 months (range 2–24), all patients had symptom resolution and no evidence of symptomatic restenosis on neuroimaging/Doppler studies; the average mRS score was 0.66. Three patients continued to have previously diagnosed mid-cervical VA stenosis; one of them had postprocedure dissection and an asymptomatic in-stent stenosis at 8 months. Conclusions: Safety and feasibility were demonstrated using the Ostial Flash system for VAO stenting and angioplasty. No permanent perioperative complications were seen.